Nusantara and Islam: a study of the history and challengesin the preservation of faith and identity - Ishak, Mohd. Shuhaimi (INSI Publications, 2014)
Background: Nusantara or the Malay Archipelago is the general term used to refer to the populace of Malays living in many parts of Southeast Asia, stretching from Vietnam, Cambodia, to Southern Thailand, Malaysia, Singapore, Indonesia, Brunei and Southern Philippines. Objective: This paper attempts to shed light on the history and challenges the Malays faced in the preservation of their faith and identity as Muslims across the Malay world. Results: Islam came to the Malay world from many locations. In addition to the Indians and Persians, the Arabs also played a role in bringing Islamic civilization to the Malays. As opposed to the teachings of the Indians and Persians who were responsible for the spread of mysticism and other popular elements of Islam, the Arabs familiarized the Malays with the orthodox teachings of the religion. Conclusion: The paper concludes that the Islamic Malay culture today is a tapestry of numerous strands as the total impact of Islamization had come from many different directions while the Malays struggled with a host of issues to maintain their faith and identity.